Human umbilical cord expresses several vasoactive peptides involved in the local regulation of vascular tone: protein and gene expression of Orphanin, Oxytocin, ANP, eNOS and iNOS - Aldo Gerbino; Salvatore Provenzano; Maria Buscemi; Annamaria Mauro (Folia Histochemica et Cytobiologica, 2011)
Full-term human umbilical cord contains three blood vessels: two arteries coiled around a vein and surrounded by Wharton’s jelly, a mucous tissue with few mesenchymal stromal cells and abundant extracellular matrix. Umbilical vessels lack innervations, thus endothelial cells must play a role in the control of blood flow. The aim of this study was to investigate in human umbilical cord the expression of five peptides that could be involved in the regulation of vascular tone: Orphanin FQ, Oxytocin, Atrial Natriuretic Peptide (ANP), endothelial Nitric Oxide Synthase (eNOS) and inducible Nitric Oxide Synthase (iNOS). The expression of these molecules in full-term human umbilical cord was investigated through immunohistochemistry and RT-PCR. Immunoreactivity for Orphanin FQ was detected in Wharton’s jelly, vessel musculature and endothelium; Oxytocin, ANP and eNOS were expressed by the umbilical epithelium, Wharton’s jelly and endothelium, whereas iNOS only by endothelial cells. RT-PCR analysis showed transcriptional expression of Oxytocin, ANP and eNOS mRNAs. The presence of Orphanin, Oxytocin, ANP, eNOS and iNOS proteins was identified in the human umbilical cord. mRNA expression for Oxytocin, ANP and eNOS suggest that these molecules are synthesized by umbilical cord cells themselves. The expression of these vasoactive molecules could be part of a general mechanism locally regulating vascular tone. (Folia Histochemica et Cytobiologica 2011; Vol. 49, No. 2, pp. 211–218)